Cash and pensions: Have the elderly in England saved optimally for retirement - Rowena Crawford; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2014)
Using a model where households can save in either a safe asset or in an illiquid, tax-advantaged pension, we assess the extent to which those who recently reached the state pension age in the UK have saved optimally for retirement. The policy environment specified closely matches that prevailing in the UK. Using the model and administrative data linked with survey data from the English Longitudinal Study of Ageing, an optimal level of wealth is calculated for each household. This is compared to the levels of wealth observed in the data. Our results show that, for those born in the 1940s, the vast majority of households have wealth levels far greater than necessary to maintain their living standards into and through retirement.
Keywords: D31; D91; E21; D12; 330; Lifecycle model; Wealth; Dynamic Programming; Savings